Patient-reported outcome measures for clinical decision-making in outpatient follow-up: validity and reliability of a renal disease questionnaire - Birgith Engelst Grove; Liv Marit Valen Schougaard; Per Ramløv Ivarsen; Derek Kyte; Niels Henrik Hjollund; Annette de Thurah (SpringerOpen, 2021)
Abstract Background Patient-reported outcome measures are increasingly used by clinicians to support communication in telephone- or face-to-face consultations with patients. A renal disease questionnaire has been developed, but not sufficiently evaluated through clinimetrics in clinical setting. Hence, we aimed to evaluate the content validity, construct validity and the test-retest reliability of a renal disease questionnaire to be used for clinical decision-making. Methods A content, construct validity and test-retest reliability study was conducted in 3 nephrology outpatient clinics in Central Denmark Region, Denmark. Content validity (face validity, comprehensibility and relevance) was assessed among 8 patients and 6 clinicians. Reliability was assessed by asking outpatients with chronic kidney disease to complete the questionnaire twice. Reliability was assessed by kappa statistics and agreement by percentage. Construct validity was determined using 4 a priori defined hypotheses and comparing 2 known groups. Results Five new domains emerged, 6 items were rephrased and 3 items were removed following the content validity test. A total of 160 patients completed the questionnaire with median 8 days (IQR 2 days) between assessments. The test-retest reliability parameters of the single items in the questionnaire were substantial to almost perfect as all the observed weighted kappa values ranged from 0.61 to 0.91, 95% CI (0.34 to 0.95). In total, 61% of the single items showed almost perfect agreement. In total, 3 of the 4 hypotheses were accepted and 44% of the items showed satisfying known-group discriminative validity. Conclusion A renal disease questionnaire used for clinical decision-making in outpatient follow-up showed acceptable content validity and substantial to almost perfect reliability. Sufficient construct validity was not established. Incorporating the questionnaire into routine clinical practice may improve the evaluation of disease burden in patients with chronic kidney disease. Plain English summary We ask patients with chronic kidney disease (CKD) in Central Region Denmark to complete a questionnaire before each outpatient visit. The answers they provide are used to support communication with their health care provider. A questionnaire requires testing to ensure it can accurately capture important information about patient's symptoms and quality of life. When questionnaires are used to support communication between patients and health care professionals, they need to have good measurement properties. This means they need to be: (1) trustworthy, (2) relevant to a patient's health condition, (3) consistent and produce stable results every time. We explored the measurement properties of a questionnaire designed to be used in the face-to face outpatient visits for patients with CKD. We found that the questionnaire captured consistent and stable results. Using this questionnaire may help health care professionals to assess the patients´ burden of symptoms with a more patient-centered approach. Potentially, the use of the questionnaire will increase the patients´ ability to cope with their symptoms and strengthen patients´ involvement in the clinical decisions concerning their treatment.